IMPLEMENTASI KEBIJAKAN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN DI RUMAH SAKIT UMUM DAERAH KABUPATEN BEKASI - Ignasia Suryani; M. Harun Al Rasyid (Governance, 2021)
In general, this study aims to find out how the implementation of BPJS Health policies and what factors influence the implementation of BPJS Health policies in Bekasi District Hospitals. This study used descriptive qualitative method. The data used is interviews with key informants of approximately one month. The results of the study indicate that in general the implementation of the BPJS Health policy at the Bekasi District Hospital is quite satisfactory, although there are still obstacles that must be overcome and repaired. According to the results of the study, based on the approach to the smooth implementation of routine functions and the approach to realizing the desired impact proposed by Randall B. Repley and Grace A. Franklin, several obstacles were found. Among them are the claims of BPJS Health participants at the Bekasi District Hospital that have not been paid by the BPJS Health and the revenue deficit experienced by the Obligation section.